Research on the Construction of a Lifelong Learning Portfolio for Early Childhood Physical Education Teachers Based on Blockchain Traceability Technology - Dai, Yuxin (Education Insights, 2026)
This study aims to develop a lifelong learning portfolio system for early childhood physical education teachers based on blockchain traceability technology. Currently, China's early childhood physical education teaching workforce faces significant challenges, such as insufficient professional competence and highly fragmented continuing education systems. Furthermore, traditional paper-based or centralized electronic portfolios exhibit substantial limitations regarding data authenticity, completeness, accessibility, and overall teacher autonomy. By analyzing the broader policy context and the practical challenges of lifelong learning for early childhood physical education teachers, and by thoroughly examining the core shortcomings of existing portfolio management models, this study proposes a robust, multi-layered system framework. This innovative architecture comprises distinct data layers, network layers, consensus layers, contract layers, and application layers. Additionally, it designs key operational processes, including secure identity authentication, continuous learning process documentation, immutable achievement certification, and authorized access queries. The study demonstrates that this decentralized system can successfully establish credible, comprehensive, self-managed, and shared lifelong learning portfolios for educators. Consequently, it not only enhances their continuous professional development but also provides highly reliable data support for employers, training institutions, and educational authorities. Ultimately, this technological integration significantly advances the professionalization and standardization of the early childhood physical education workforce. Finally, the report analyzes potential technical and non-technical challenges in system implementation and outlines future development prospects for blockchain in educational management.